KEPENTINGAN NASIONAL CHINA DALAM KONFLIK LAUT CINA SELATAN - Harini, Setyasih (Transformasi, 2011)
Abstract This article explores about national interest of China in conflict of South China Sea. The South China Sea is rich in potencial natural resources especially hydrocarbons – oil and natural gas and fishery resources. It’s also strategic international sea. But this is semi enclosed sea that surrounded ten coast countries and six of them are included in overlapping claims and territorial disputes. China, Vietnam, Malaysia, Philippines, Brunei Darussalam, and Taiwan all have made claims teritorial sovereignty to various rights in that body of water. So The South China Sea is important to China not only for its strategic location but also because of its natural resources. For China, claim about The South China Sea is a core interest and to protect its core interest with military means because it was believed as a Chinese Lake. From economic, the national interest of China is that The South China Sea is used to enhance the economic reforms and promoting its economic development. As consequence of economic reforms make China to refind the new natural resources. The China successful of claim in The South China Sea can show the big power for another countries not only in Southeast Asia or East Asia (regional) and international. Keywords: power, national interest, conflict, natural source